2020
DOI: 10.1111/are.14550
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary astaxanthin on growth, blood biochemistry, antioxidant, immune and inflammatory response in lipopolysaccharide‐challengedChanna argus

Abstract: The present study investigated the effects of dietary astaxanthin on the growth, blood biochemical, antioxidant, immune and inflammatory response in lipopolysaccharide‐challenged Channa argus. A total of 0, 50, 100 and 200 mg/kg of astaxanthin were added to the basal die for 56 days. After the feeding experiment, each group was subjected to a lipopolysaccharide challenge (except for the Control group). The results showed that adding astaxanthin to the diet can significantly increase the weight gain and specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 52 publications
(60 reference statements)
4
14
0
Order By: Relevance
“…LZM and NO are the component of fish innate immune system and immunoactive substance (Nathan, 1992; Saeij et al, 2002; Saurabh & Sahoo, 2008). In the present study, results of LZM activity and NO content were similarly to the red swamp crayfish (Cheng & Wu, 2019) and Channa argus (Zhu et al, 2020), indicating that Ast may provide the immune resistance of large yellow croaker larvae through the immunity enzymes (De Pascali et al, 2019).…”
Section: Discussionsupporting
confidence: 71%
“…LZM and NO are the component of fish innate immune system and immunoactive substance (Nathan, 1992; Saeij et al, 2002; Saurabh & Sahoo, 2008). In the present study, results of LZM activity and NO content were similarly to the red swamp crayfish (Cheng & Wu, 2019) and Channa argus (Zhu et al, 2020), indicating that Ast may provide the immune resistance of large yellow croaker larvae through the immunity enzymes (De Pascali et al, 2019).…”
Section: Discussionsupporting
confidence: 71%
“…43 Studies have also shown that astaxanthin helped to stabilize lipid in food products, thereby preventing any rancidity that could render foods unfit for consumption. 55 Wang et al 56 and Zu et al 57 reported that astaxanthin, irrespective of the amount, improved growth performance in animals. In addition, the MSCD group had a high content of sulphur amino acids, especially methionine, which is indispensable for protein synthesis and hence growth.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al 56 . and Zu et al 57 . reported that astaxanthin, irrespective of the amount, improved growth performance in animals.…”
Section: Resultsmentioning
confidence: 99%
“…It has curative and preventive effects against inflammation, infectious diseases, and oxidative stress [ 54 ]. However, although some research has shown the positive effect of astaxanthin on the immune and inflammatory systems [ 55 , 58 , 59 ], other research presented no such particular changes [ 60 , 61 ]. In our study, regardless of the supplementation dose, astaxanthin did not affect IgM and IgG activities in serum.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the aforementioned studies dealing with astaxanthin to improve the immune system were for the most implemented on vaccinated or challenged animals. Zhu et al [ 59 ] claimed that fishes show defensive responses under the stimulus of external environment; then, granulocytes and white blood cells are activated to stimulate the inflammatory response and release inflammatory factors. Without challenge, immunoglobulins are less stimulated.…”
Section: Discussionmentioning
confidence: 99%